2023
DOI: 10.2196/39568
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Dialysis Care in Mainland China: Nationwide Survey

Abstract: Background Peritoneal dialysis (PD) care in mainland China has been progressing in the past 10 years. Objective To complement information from the dialysis registry, a large-scale nationwide survey was conducted to investigate the current infrastructure and management of PD care at hospitals of different tiers. Methods A web-based multiple-choice questionnaire was distributed through the National Center for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…The detection rate of esophageal cancer (early and advanced stage) was 0.3% (5 of 1556), which was substantially higher than the national average of 24.0 per 100,000 person-years ( 18 ). Recently, a meta-analysis reported that the pooled rate of positive cases (including esophageal cancer and precancerous lesions) was 1.03% in the high-risk areas ( 19 ). Japan, a country with a high incidence of esophageal cancer, has a national crude incidence of esophageal cancer of about 37.0 per 100,000 person-years, but its early detection rate of esophageal cancer is more than 70% ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…The detection rate of esophageal cancer (early and advanced stage) was 0.3% (5 of 1556), which was substantially higher than the national average of 24.0 per 100,000 person-years ( 18 ). Recently, a meta-analysis reported that the pooled rate of positive cases (including esophageal cancer and precancerous lesions) was 1.03% in the high-risk areas ( 19 ). Japan, a country with a high incidence of esophageal cancer, has a national crude incidence of esophageal cancer of about 37.0 per 100,000 person-years, but its early detection rate of esophageal cancer is more than 70% ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…PD is an important treatment modality for patients with end-stage renal disease (ESRD) in China [ 12 ], and the quality of PD strongly influences the prognosis of ESRD patients [ 13 ]. PD often has peritonitis, catheter-related infection, mechanical complications, and other risks, which can eventually lead to stopping PD, switching to hemodialysis or receiving renal transplantation, and even death in severe cases, which is extremely detrimental to patients.…”
Section: Discussionmentioning
confidence: 99%
“…Peritonitis is a prevalent inflammatory disease characterized by clinical manifestations such as diarrhea, abdominal pain, abdominal infection, and multiple organ failure, with a mortality rate exceeding 60% [6,7]. Despite the incomplete elucidation of the pathogenic mechanisms underlying this disease, extensive reported research suggests a close association between peritonitis and macrophages [8,9].…”
Section: Introductionmentioning
confidence: 99%